Proper doses of brassinolide enhance somatic embryogenesis in different competent Korean pine cell lines during embryogenic callus differentiation - Nie, Shuai; Yan, Yong; Wang, Yue; Liu, Shanshan; Guo, Wenhui; Yang, Ling; Shen, Hailong (Frontiers in Plant Science, 2024)
Somatic embryogenesis of Korean pine (Pinus koraiensis Sieb. Et Zucc.), an ecologically and econimically very important conifer species, was hindered by the gradually weakens and fast runaway of the embryogenicity and embryo competence of the embryogenic callus. Brassinolide (BL) has shown the enhancing capability of somatic embryo regeneration. For checking the function of BL in this issue, we applied different concentrations of BL to Korean pine callus materials exhibiting different embryogenic capacities and subsequently monitored the physiological alterations and hormone dynamics of the embryogenic callus. Our study revealed that calli with different embryogenic strengths responded differently to different concentrations of BL, but the effect after the addition of BL was very uniform. The addition of BL during the proliferation phase of embryogenic callus may help to stimulate the biological activity of callus during the proliferation process and improve the level of cell metabolism, which is accompanied by a reduction in storage substances. BL could reduce the level of endogenous auxin IAA in embryogenic callus and increase the level of abscisic acid to regulate cell division and differentiation. In addition, the MDA content in the callus was significantly decreased and the activity of antioxidant enzymes was significantly increased after the addition of BL. During the proliferation of embryogenic callus, BL was added to participate in the metabolism of phenylpropane in the cells and to increase the activity of phenylalanine ammonia-lyase and the content of lignin in the cells. We deduced that the proper doses of BL for Korean pine embryogenic callus culture were as follow: calli with low, high and decreasing embryogenicity were subcultured after the addition of 0.75 mg/L, 0.35 mg/L, 2.00 mg/L BL, respectively, during proliferation culture stage.